Efficacy of HCV treatment in Poland at the turn of the interferon era – the EpiTer study - Flisiak, Robert; Pogorzelska, Joanna; Berak, Hanna; Horban, Andrzej; Orłowska, Iwona; Simon, Krzysztof; Tuchendler, Ewelina; Madej, Grzegorz; Piekarska, Anna; Jabłkowski, Maciej; Deroń, Zbigniew; Mazur, Włodzimierz; et al. (Clinical and Experimental Hepatology, 2016)
The aim of the study was to analyze the efficacy achieved with regimens available for chronic hepatitis C (CHC) in Poland between 2013 and 2016. Material and methods : Data were collected from 29 centers and included 6786 patients with available sustained virologic response (SVR) data between 1 January 2013 and 31 March 2016. Results : The sustained virologic response rate for genotypes (G) 1a, 1b, 2, 3 and 4 was 62%, 56%, 92%, 67% and 56% respectively; 71% patients (n = 4832) were treated with pegylated interferon  (Peg-IFN) and ribavirin (RBV), with SVR rates of 58%, 49%, 92%, 67% and 55% respectively. The sustained virologic response among 5646 G1 infected patients was the lowest with natural interferon  (7%, n = 70) or PegIFN (50%, n = 3779) with RBV, and improved in those receiving triple regimens of Peg-IFN + RBV combined with boceprevir (47%, n = 485), telaprevir (64%, n = 805), simeprevir (73%, n = 132) or sofosbuvir (70%, n = 23). The sustained virologic response with interferon-free regimens of sofosbuvir and RBV (n = 7), sofosbuvir and simeprevir (n = 53), and ledipasvir and sofosbuvir (n = 64) achieved 86%, 89% and 94% respectively. The highest SVR of 98% was observed with ombitasvir/paritaprevir combined with dasabuvir (n = 227). Patients infected with G3 (n = 896) and G4 (n = 220) received mostly Peg-IFN + RBV with SVR of 67% and 56% respectively. Interferon-free regimens were administered in 18 G3/G4 patients and all achieved an SVR. Sofosbuvir combined with Peg-IFN and RBV was administered to 33 patients with an SVR rate of 94%, and a similar rate was achieved among 13 G2 patients treated with interferon and RBV. Conclusions : We observed significant differences in efficacy of HCV regimens available in Poland at the turn of the interferon era. The data will be useful as a comparison for therapeutic options expected in the next few years.